Menumbuhkan Perilaku Konsumsi Dan Produksi Bertanggung Jawab Melalui Pendidikan Agama Islam - Sri Munarti; Eko Setiono; Dafik Fadli (FKIP UNSULTRA, 2025)
Irresponsible consumption and production behavior is one of the causes of increasing environmental damage, waste of resources, and weakening moral awareness in modern society. Islamic Religious Education (PAI) plays a strategic role in shaping students' mindsets and behaviors to align with Islamic values ​​that emphasize balance, simplicity, and responsibility towards nature. This literature study aims to analyze how PAI can contribute to fostering responsible consumption and production behavior through the integration of Islamic ethical values. The method used is a literature review of journals, books, and relevant research results on consumption ethics in Islam, character education, and PAI learning practices. The results of the study indicate that key concepts in Islam such as the prohibition of isrāf (excess), tabdzīr (waste), the principle of mīzān (balance), and amanah (trust) in utilizing resources, provide a strong moral foundation for shaping sustainable consumption and production behavior. PAI serves as an effective educational tool through the integration of these values ​​into the curriculum, learning models, and daily practices of students. Project-based learning, teacher role models, and a contextual approach have proven effective in instilling ecological awareness and ethical consumption. This study concludes that Islamic Religious Education (PAI) not only serves as a transfer of religious knowledge but also as an instrument for developing ecological character that supports the creation of a sustainable society.